Synergies at the interface of farmer-scientist partnerships: agricultural innovation through participatory research and plant breeding in Honduras - Humphries, S.; Rosas, J.C.; Gómez, M.; Jiménez, J.; Sierra F; Gallardo O; Ávila, C.; Barahona, M. (Springer, 2015)
Background: The article describes the institutionalization of farmer participatory research and plant breeding that has occurred in Honduras over the past 22 years and demonstrates how this approach can offer a positive response to climate change and sustainable agricultural development. In Honduras, participatory plant breeding (PPB) involves the collaboration of farmer researchers organized in local agricultural research committees (CIALs), plant breeders, and non-governmental organizations (NGOs). While earlier debates often questioned the role of farmers in agricultural research, particularly the synergistic effect of this role with regard to scientific research, little empirical evidence was provided to settle this debate. Nor was the contextualization of farmer research adequately addressed. The article responds to calls for studies that detail what actually happens in development practice.